DNA methylation changes underlie the long-term association between periodontitis and atherosclerotic cardiovascular disease - Omar, Mohamed; Alexiou, Maria; Rekhi, Umar R.; Lehmann, Konrad; Bhardwaj, Aneesh; Delyea, Cole; Elahi, Shokrollah; Febbraio, Maria (Frontiers in Cardiovascular Medicine, 2023)
Periodontitis, the leading cause of adult tooth loss, has been identified as an independent risk factor for cardiovascular disease (CVD). Studies suggest that periodontitis, like other CVD risk factors, shows the persistence of increased CVD risk even after mitigation. We hypothesized that periodontitis induces epigenetic changes in hematopoietic stem cells in the bone marrow (BM), and such changes persist after the clinical elimination of the disease and underlie the increased CVD risk. We used a BM transplant approach to simulate the clinical elimination of periodontitis and the persistence of the hypothesized epigenetic reprogramming. Using the low-density lipoprotein receptor knockout (LDLRo) atherosclerosis mouse model, BM donor mice were fed a high-fat diet to induce atherosclerosis and orally inoculated with Porphyromonas gingivalis (Pg), a keystone periodontal pathogen; the second group was sham-inoculated. Naïve LDLRo mice were irradiated and transplanted with BM from one of the two donor groups. Recipients of BM from Pg-inoculated donors developed significantly more atherosclerosis, accompanied by cytokine/chemokines that suggested BM progenitor cell mobilization and were associated with atherosclerosis and/or PD. Using whole-genome bisulfite sequencing, 375 differentially methylated regions (DMRs) and global hypomethylation in recipients of BM from Pg-inoculated donors were observed. Some DMRs pointed to the involvement of enzymes with major roles in DNA methylation and demethylation. In validation assays, we found a significant increase in the activity of ten-eleven translocase-2 and a decrease in the activity of DNA methyltransferases. Plasma S-adenosylhomocysteine levels were significantly higher, and the S-adenosylmethionine to S-adenosylhomocysteine ratio was decreased, both of which have been associated with CVD. These changes may be related to increased oxidative stress as a result of Pg infection. These data suggest a novel and paradigm-shifting mechanism in the long-term association between periodontitis and atherosclerotic CVD.